1992
DOI: 10.1136/gut.33.12.1626
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD2 and anti-CD3 induced T cell cytotoxicity of human intraepithelial and lamina propria lymphocytes.

Abstract: The effector function of immunocompetent cells in the gut mucosa has not yet been defined. The Changes in cell mediated cytotoxicity of intraepithelial lymphocytes and lamina propria lymphocytes may be involved in the mucosal damage in these inflammatory conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Our results are consistent with previous reports which show that human IEL exert spontaneous cytotoxicity against tumour target cells [13,17]. On the other hand, it is reported that human IEL exhibit cytotoxicity only after in vitro activation with mitogens, IL-2 [18], or ligation of CD2 and CD3 [19]. In these studies, the cytotoxic function was evaluated by 51 Crrelease assay, which may be less sensitive in detecting Fas-FasLmediated cytotoxicity compared with the 3 H-thymidine release assay used in this study.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with previous reports which show that human IEL exert spontaneous cytotoxicity against tumour target cells [13,17]. On the other hand, it is reported that human IEL exhibit cytotoxicity only after in vitro activation with mitogens, IL-2 [18], or ligation of CD2 and CD3 [19]. In these studies, the cytotoxic function was evaluated by 51 Crrelease assay, which may be less sensitive in detecting Fas-FasLmediated cytotoxicity compared with the 3 H-thymidine release assay used in this study.…”
Section: Discussionsupporting
confidence: 93%
“…An indirect approach takes advantage ofthe fact that MoAbs specific for the T cell receptor (TCR)/CD3 complex can induce antigen-independent cytotoxicity of in vivo primed CTL [7]. Patients with IBD have an apparent increase in anti-CD3-triggered CTL in peripheral blood, suggesting a change in immune activity [8]; however, the nature of this activity in mucosal T cells of CD patients is not clear [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…IELs play an important role in protection from epithelial tumor cells through their function as cytolytic agents (37). Lamina propria lymphocytes (LPLs), also mainly T cells, are derived from the thymus; they constitute primarily the ␣␤ form of the TCR (12) and have some cytolytic activity against tumor cell lines (38). CD8 T lymphocytes, compromising two subpopulations of ␣-and ␤-chain phenotypes, have cytolytic functions and are found in both the intraepithelial and lamina propria regions (4).…”
mentioning
confidence: 99%